Macroeconomics : - Barro, Robert J. (Thomson South-Western, 2008)
Material presented in this book includes lots of hand wavy intuitive arguments aimed at an audience who fear algebra - let alone calculus. If you have a firm grasp of financial math and a high school reading level than the extra 'proofs' may actually distract you from discerning the two or three kernels of knowledge contained in any given chapter.